Informational And Didactic Modeling Of The Content Of The E-Textbook On The Mechanization Of Agricultural Production On The Basis Of The Ontological Approach - Rostoka, M.; Guraluk, A. (Problems of Engineer-Pedagogical Education, 2019)
The authors raise the problem of new approaches in the field of creating textbooks, analyze the Ukrainian experience gained in the didactic modeling of electronic textbooks for vocational and post-school education, which should be of interest to a wide range of users. The authors suggest organizing an e-textbook environment on the mechanization of agricultural production on the basis of an ontological approach to ensure both the process of training future skilled fruit and vegetable growers in vocational (vocational and technical) education institutions, and to conduct research work in the agricultural sector by means of extracurricular educational activities, in particular within the system of the Junior Academy of Sciences of Ukraine. The article also analyzes the scientific and pedagogical literature, regulatory documents and sources of databases on the identified issues. The information and didactic substantiation of modeling the content and structure of the electronic textbook is presented. The authors demonstrate the general hierarchical structure of a typical curriculum on the logic of information and didactic modeling of an e-textbook on the professionally relevant specialized discipline, i.e. mechanization of agricultural production, and also offer its generalized structural model in accordance with the requirements of DSPTO 6111. ОА.01.10-2014 “Fruit and vegetable grower”. It is emphasized that there is a certain technological system for establishing relationships between didactic resource units. They are considered to be combined into enlarged didactic units, the assimilation of which indicates the existing level of formation of professional competence of future fruit and vegetable growers in terms of their acquisition of professional knowledge and skills (professional competencies) in the implementation of fruit and vegetable mechanized growing. Attention is focused on the features of technological editing of this e-textbook when it is introduced into the practice of education in Ukraine, and the advantages and obstacles to this process are determined.